Cognitive Behavior vs Bright Light Therapy for Insomnia in Women Undergoing Chemotherapy for Breast Cancer - Trang Thuy Do; Jordan Maccora; Rebecca Wallace; Veronica Aedo-Lopez; Marliese Alexander; Sonia Ancoli-Israel; Bei Bei; Robert Blum; Frances Boyle; Daphne Day; Justine Diggens; Prudence A. Francis; et al. (JAMA Network Open, 2026)
Importance Women receiving chemotherapy for breast cancer experience insomnia and fatigue, which impair quality of life. To date, no randomized clinical trial (RCT) has evaluated the use of cognitive behavior therapy for insomnia (CBT-I) and bright light therapy (BLT) both alone and in combination, and few have evaluated the use of either during chemotherapy. Objective To determine the main effects of CBT-I and BLT on insomnia and fatigue symptoms in women undergoing chemotherapy for breast cancer. Design, Setting, and Participants Sleep, Cancer, Rest (SleepCARE) was a 6-week, 2 × 2 factorial, superiority, parallel RCT conducted at 5 metropolitan and regional hospitals in Australia from January 22, 2021, to August 21, 2024. Participants were women (aged ≥18 years) receiving chemotherapy for early or metastatic breast cancer. Interventions Two brief interventions were administered: CBT-I and BLT alone (using light glasses at 1500 lux) and in combination, creating 4 groups (CBT-I alone, BLT alone, CBT-I plus BLT, and sleep hygiene education [SHE]). All interventions included SHE. The interventions lasted 6 weeks and included a 1:1 consultation session, emails sent once or twice per week, and a midpoint call for all groups, as well as light glasses for the BLT groups. Main Outcomes and Measures Dual primary outcomes were Insomnia Severity Index (ISI) scores and Patient-Reported Outcomes Measurement Information System (PROMIS)–Fatigue T scores. Both are patient-reported outcome measures and measure insomnia and fatigue symptoms, respectively. Assessments occurred via surveys administered at baseline and at the midpoint (3 weeks), postintervention (6 weeks), and follow-up (3 months and 6 months) periods. Modified intention-to-treat analyses used latent growth models. Results Of the 219 women enrolled (mean [SD] age, 50.7 [10.8] years; 54 [26.9%] with metastatic cancer), 55 were randomized to CBT-I, 55 to BLT, 52 to CBT-I plus BLT, and 57 to SHE. A total of 208 women (95.0%) with any data at any time point were analyzed. Insomnia symptoms (ISI score mean difference [MD], −2.19 [95% CI, −3.33 to −1.05] points; P = .002) but not fatigue symptoms (PROMIS-Fatigue score MD, −0.90 [95% CI, −3.08 to 1.28] points; P = .52) improved more in the CBT-I groups compared with the non–CBT-I groups. The BLT groups (compared with the non-BLT groups) did not differ in insomnia symptoms (ISI score MD, −0.88 [95% CI, −2.02 to 0.26] points; P = .26) or fatigue symptoms (PROMIS-Fatigue score MD, −0.71 [95% CI, −2.89 to 1.47] points; P = .52). Comparable results emerged in the high-adherence subgroup and in the subgroups with high initial insomnia and fatigue symptoms. However, exploratory subgroup analyses in women with metastatic breast cancer showed that BLT (vs non-BLT) improved insomnia symptoms (ISI score MD, −2.87 [95% CI, −5.06 to −0.67] points; P = .01) and fatigue symptoms (PROMIS-Fatigue score MD, −5.16 [95% CI, −9.57 to −0.76] points; P = .02). Conclusions and Relevance In the SleepCARE RCT of CBT-I and BLT administered for 6 weeks to women receiving chemotherapy for breast cancer, CBT-I improved insomnia but not fatigue compared with SHE or BLT. BLT did not produce greater improvements in fatigue or insomnia symptoms compared with non-BLT treatment. The study findings indicate that brief CBT-I, but not BLT, may reduce insomnia symptoms among women receiving chemotherapy for breast cancer. Trial Registration ANZCTR Identifier: ACTRN12620001133921